CAF-derived exosomes drive the FGF4/SHH feedback loop by encapsulating GREM1 in non-small cell lung cancer - Xianqiao Wu; Wei Chen; Tianzheng Fang; Ziyuan Chen; Shuai Fang; Chengwei Zhou (Molecular Medicine)
Abstract Background One of the hallmarks of a pre-metastatic niche (PMN) is the infiltration of immunosuppressive macrophages, while the mechanism remains largely uncharted. Here, we reveal that cancer-associated fibroblasts-derived exosomes (CAF-exo) polarize macrophages towards an immunosuppressive phenotype through encapsulating Gremlin-1 (GREM1) in non-small cell lung cancer (NSCLC). Methods CAF and normal fibroblasts (NF) were extracted from NSCLC patients, and the exosomes produced were extracted. The effects of NF- or CAF-derived exosomes on the expression of PMN-associated markers and macrophage M2 polarization markers in mouse lung and liver tissues were compared. CAF-exo-mediated macrophage phenotypic switching and immunosuppressive effects on T cells were studied in vitro. Orthotopic lung tumors were formed in mice using Lewis lung carcinoma (LLC) cells, followed by CAF-exo treatment. CAF-exo with GREM1 knockdown were used to treat macrophages or the LLC model mice. Finally, the reciprocal regulation between GREM1 and FGF4/SHH in macrophages was revealed, and rescue experiments were conducted. Results Intravenous injection of CAF-exo induced an immunosuppressive phenotype of macrophages in lung and liver tissues, leading to PMN formation. Tumor progression promoted by CAF-exo was blocked by knocking down GREM1 in CAF-exo. CAF-exo-derived GREM1 activated FGF4/SHH signaling in macrophages, and knockdown of FGF4/SHH inhibited macrophage M2 polarization. Ectopic expression of SHH or FGF4 activated GREM1/FGF4/SHH signaling and rescued the anti-tumor effects of GREM1 knockdown in vivo. Conclusions CAF-exo activated the positive feedback regulation of FGF4/SHH and GREM1 in macrophages by carrying GREM1, leading to the switch of macrophages to an immunosuppressive phenotype and PMN formation in NSCLC.